Cardiopulmonary Bypass through a Left Thoracotomy Using Venous Drainage from the Innominate Vein in Congenital Heart Surgery. Issue 5 (28th July 2013) - Suzuki, Takaaki; Masuoka, Ayumu; Uno, Yoshimasa; Iwazaki, Mika; Yamagishi, Syunsuke; Katogi, Toshiyuki
Abstract Cardiopulmonary bypass (CPB) through a left lateral thoracotomy is a useful approach for some congenital heart procedures, although vascular access for the arterial and venous cannulation can be challenging in the selective patients. Six patients underwent successful extracorporeal circulation through a left lateral thoracotomy using the innominate vein for venous drainage. No operative deaths or major complications occurred. Venous drainage solely from the innominate vein was adequate to establish partial bypass without the need for pericardiotomy. Total bypass was established with combined venous drainage from the innominate vein and the main pulmonary artery. Exposure of the systemic atrioventricular valve was excellent through a left thoracotomy. Venous drainage from the innominate vein without using atrial drainage can safely be used for extracorporeal circulation through a left lateral thoracotomy without compromising the procedure and it is a useful approach to congenital heart surgery in selected patients. doi: 10.1111/jocs.12165 (J Card Surg 2013;28:591–594)